Environmental Health and Welfare as an Important Aspect of Civilizational Islam - Bakar, Osman (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Environmental Health and Welfare as an Important Aspect of Civilizational Islam